The OECD's narrative on the future curriculum: issuing values - Berit Karseth; Simona Bernotaite; Anniken Hotvedt Sundby (Taylor & Francis Group, 2024)
This paper explores the work of a particular document in issuing educational values. The document is the report Embedding Values and Attitudes in Curriculum: Shaping a Better Future, launched in 2021 and published by the Organisation for Economic Co-operation and Development (OECD). Inspired by a practice-oriented method of document analysis and the concepts of modifying work and contexting, we show how the issue of values is modified and transformed through the text. We illustrate how different data is used in the transformation with examples from the Nordic countries. Our analysis revealed five modifications that transformed the issue of values from a global societal issue embedded in international and national regulations to an issue defined by the OECD's Learning Compass and its nine competencies. The report gives prominence to the individual learner and competencies needed to navigate towards a future of well-being. Hence, the issue of values is reduced to universal competencies, and the report can manoeuvrer its argument to avoid issuing values as something controversial. Finally, we argue that the ways in which values are issued implies a curriculum design that is not compatible with the traditional curriculum format based on didaktik and Nordic ambitions.